The rez doctor - Crazyboy, Gitz (HighWater Press, 2024)
"In this uplifting story, a young Indigenous man overcomes hardship to fulfill his dream of becoming a doctor. Young Ryan Fox gets good grades, but he's not sure what he wants to be when he grows up. It isn't until he meets a Blackfoot doctor during a school assembly that he starts to dream big. However, becoming a doctor isn't easy. University takes Ryan away from his family and the Siksikaitsitapi community, and without their support, he begins to struggle. Faced with more stress than he's ever experienced, he turns to partying. Distracted from his responsibilities, his grades start to slip. His bills pile up. Getting into med school feels impossible. And now his beloved uncle is in jail. Can Ryan regain his footing to walk the path he saw so clearly as a boy? This inspiring graphic novel for young adults is based on a true story."--